Evaluating Global Zakat Game (GZG) board game in enhancing Zakat education - Azman Ab. Rahman; Muhammad Sabri bin Sahrir; Nurkhamimi Zainuddin; Hasanah Abd Khafidz (Journal of Education and Learning (EduLearn), 2018)
Many educators have chosen to use board games to enhance the way of delivering course contents. A board game will help students understand an education concept quickly through experiential learning, where they manage and solve problems in a real situation. This study is focusing on the evaluation of a board game, namely Global Zakat Game (GZG) as an edutainment tool among various levels of users at learning institutions in Malaysia. The respondents were purposively selected from a Malaysian national competition organized at Islamic Science University of Malaysia (USIM) on 8 November 2017. A questionnaire was distributed among 235 participants from various levels of learning institutions during the national event to evaluate the practical use of GZG as an edutainment tool in increasing their understanding on Zakat theories and practice. The result indicated that the use of GZG as a Zakat edutainment tool has a positive impact on users and players as it helps them to learn more about Zakat theories and practice between high (4.65) and moderate high (3.95) of mean scores. Most of the respondents mentioned that they enjoyed playing GZG as it involves experiential learning and learning by doing.